Pharmacokinetics of flupirtine in elderly volunteers and in patients with moderate renal impairment. Issue 751 (May 1988) - Abrams, S. M.; Baker, L. R.; Crome, P.; White, A. S.; Johnston, A.; Ankier, S. I.; Warrington, S. J.; Turner, P.; Niebch, G.
Abstract : The pharmacokinetics of flupirtine after a single oral dose of 100mg have been studied in patients with moderate renal impairment and in healthy elderly subjects aged 66-83 years. Mean elimination half-life of flupirtine was higher in elderly patients than in younger normal subjects, and this was associated with an increased maximum serum concentration and reduced clearance. The mean half-life in patients with renal impairment was higher than in normal subjects. There was no correlation between observed elimination half-life and degree of renal impairment, but the creatinine clearance of most patients fell in a narrow range between 43 and 60 ml/min. In the light of these results and until further information is available, it would be prudent to start treatment of patients who are elderly or have evidence of renal impairment with half the dose of flupirtine recommended for younger patients with normal renal function.